2018
DOI: 10.1177/0954406218756943
|View full text |Cite
|
Sign up to set email alerts
|

Robust genetically optimized skew laminates

Abstract: The present research work explores genetically optimized skew laminates, whose stacking sequence has been varied to maximize their fundamental frequencies with the help of an efficient optimization algorithm. Genetic algorithm, rather than being applied blindly with empirical parameters, is tuned with respect to the problem at hand. Following an extensive study, genetic algorithm parameters are selected carefully so as to ensure a robust optimized stacking sequence. The sensitivity of ply angles is also invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 26 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Based on past research works on the same finite element formulation [30][31][32], it is revealed that an 18 × 18 mesh discretization of the composite plate using 9-node isoparametric elements is sufficiently accurate for the considered problems. To demonstrate the accuracy of the current FEM formulation, a validation example is included in Figure A1, Appendix A.…”
Section: Finite Element Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on past research works on the same finite element formulation [30][31][32], it is revealed that an 18 × 18 mesh discretization of the composite plate using 9-node isoparametric elements is sufficiently accurate for the considered problems. To demonstrate the accuracy of the current FEM formulation, a validation example is included in Figure A1, Appendix A.…”
Section: Finite Element Methodsmentioning
confidence: 99%
“…These three natural frequencies are treated here as the responses. The detailed formulation of the FEM used in this paper can be available in [30][31][32]. The FE formulation adopts a 9-node isoparametric element and is based on first-order shear deformation theory (FSDT).…”
Section: Problem 1: Low-dimensional (Ld) Problemmentioning
confidence: 99%
“…The objective is to identify and inhibit bot threats and improve the performance of botnet detection. The GA is a metaheuristic algorithm inspired by natural selection and evolution [31]. It involves using a population of candidate solutions (in this case, features) that undergo selection, crossover, and mutation operations to evolve towards an optimal solution.…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…Selecting the key parameters of GA, such as population size, number of generations, crossover rate and mutation rate, carefully is extremely important. 29,30 This algorithm regards all individuals in the population as research objects and achieves a stable, optimal breeding and selection process through the hybridisation and variation of individual genes, until the population puts forward the best solution. 31 Compared with traditional algorithms, GAs use global optimisation rather than point-to-point search, making it easier to achieve global optimality.…”
Section: Mathematical Model Of Ga-bpnnmentioning
confidence: 99%